Creativity of program producer ‘Inside Indonesia’ CNN Jakarta - Sarifah, Siti; Setio Utomo, Ardian (COMMICAST, 2024)
The creativity of the Inside Indonesia Program Producer is essential in its production, so the producer must be able to think and express ideas or thoughts in writing. This research aims to discover what creativity producers have in the Inside Indonesia program, which can later be used as a reference for future productions. This research uses a qualitative approach to see how to manage a media company in the current era, specifically looking at how creative producers face media competition in the digital era at CNN Jakarta. The results of this research show that there is some producer creativity that has been carried out in producing the Inside Indonesia Program, such as different thinking carried out by the team by determining the best image and best soundbite, as well as including elements of paradox and conflict, the ability to find unusual solutions to a problem, The stages of the production process for the Inside Indonesia Program went through the production process, Pre-Production, Production, and Post-Production. The creative elements of creation, change, development, and imitation in this program can be seen starting from the creation of existing ideas/concepts, changes based on evaluations carried out, and development by looking at existing developments as well as the creation of new ideas according to current audience/market demands.